Effect of Grinded of Debris of Concrete on the Compressive Strength of Reactive Powder Concrete (Journal of University of Babylon for Engineering Sciences, 2018)
This investigation is an attempt to increase the sensibility of sustainability in the construction industry through studying the influence of the replacement part of cement (C) or silica fume (SF) content with a Grinded Debris of Concrete (GDC) on the compressive strength (fcu) of Reactive Powder Concrete (RPC). Reference RPC mix without GDC and other six RPC mixes with GDC are designed, mixed, molded and tested. Three mixes are designed to show the effects of replacement 5%, 10% and 15% of C with GDC. While, the other three are designed to show the effects of replacement 10%, 20% and 30% of SF with GDC.The results exhibited that high (fcu) can be achieved by involving the GDC in the mixes of RPC. However, a very little negative effect on (fcu) can be noticed. This effect differs according to the type of the replaced material, percentage of replacement and the age of concrete. The impact of replacing a part of C with GDC is clearer than that of replacing a part of SF with GDC. Increasing the percentage of replacement leads to decrease the values of (fcu). GDC has a very close action as SF especially at later ages.